Unlikely Nomads: Settlement, Establishment, and Dislodgement Processes of Vegetative Seagrass Fragments - Lai, Samantha; Yaakub, Siti Maryam; Poh, Tricia S. M.; Bouma, Tjeerd J.; Todd, Peter A. (Frontiers in Plant Science, 2018)
The dispersal of seagrasses is important to promoting the resilience and long-term survival of populations. Most of the research on long-distance dispersal to date has focused on sexual propagules while the dispersal of vegetative fragments has been largely overlooked, despite the important role this mechanism might play. In this study, we propose a conceptual model that categorises vegetative fragment dispersal into seven fundamental steps: i.e., i) fragment formation, ii) transport, iii) decay, iv) substrate contact, v) settlement, vi) establishment, and vii) dislodgement. We present two experiments focusing on the final steps of the model from substrate contact to dislodgement in four tropical seagrass species (Cymodocea rotundata, Halophila ovalis, Halodule uninervis, Thalassia hemprichii), which are critical for dispersed vegetative fragments to colonise new areas. We first conducted a mesocosm experiment to investigate the effect of fragment age and species on settlement (i.e., remains on the substrate in a rising tide) and subsequently establishment (i.e., rooting in substrate) rates. To determine dislodgement resistance of settled fragments, we also subjected fragments under different burial treatments to wave and currents in a flume. We found that both initial settlement and subsequent establishment rates increased with fragment age. H. ovalis was the only species that successfully established within the study period. After settlement, dislodgement resistance depended primarily on burial conditions. Smaller species H. ovalis and H. uninervis were also able to settle more successfully, and withstand higher bed shear stress before being dislodged, compared to the larger species T. hemprichii and C. rotundata. However, the ordinal logistic regressions did not reveal relationships between the tested plant morphometrics and the energy needed for dislodgement (with the exception of C. rotundata), indicating that there are potentially some untested species-specific traits that enable certain species to withstand dislodgement better. We discuss the implication our findings have on the dispersal potential for different species and the conservation of seagrasses. This study represents the first effort towards generating parameters for a bio-physical model to predict vegetative fragment dispersal.